2009
DOI: 10.5433/1679-0359.2009v30n2p389
|View full text |Cite
|
Sign up to set email alerts
|

Influência do nível de irradiância no crescimento, produção e composição química do óleo essencial de hortelã-do-campo (Hyptis marrubioides Epl.)

Abstract: In the present work, the level of irradiation of 20, 60 and 100% of natural light on the growth, content and composition of the essnetial oil of "hortelã do campo" (Hyptis marrubioides) was evaluated.The experiment was conducted in the completely randomized design with twenty-five replicates per treatment. After 132 days of cultivation, plant growth and the content and compositoin of the essntial oil were investigated. At 100% of irradiation, the plants presented less height as compared with the shaded treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 3 publications
1
3
0
2
Order By: Relevance
“…Plants subjected to greater available light tend to have shorter LMs because of the plant's greater photosynthetic investment in producing secondary branches (Sales et al, 2009). In this study, the longest LM was observed in the most lighted environments, as was the case in regard to number of internodes.…”
Section: Discussionsupporting
confidence: 52%
“…Plants subjected to greater available light tend to have shorter LMs because of the plant's greater photosynthetic investment in producing secondary branches (Sales et al, 2009). In this study, the longest LM was observed in the most lighted environments, as was the case in regard to number of internodes.…”
Section: Discussionsupporting
confidence: 52%
“…In T. riparia, the main component of the essential oil was the sesquiterpene hydrocarbon 14-hydroxy-9-epi-(E)-caryophyllene, regardless of the irradiance level under which plants were grown (Table 2). Similar results were obtained for all irradiance levels for Hyptis marrubioides Epl., where the major component of the essential oil was the oxygenated monoterpene cis-thujone (Sales et al, 2009), and for Mentha x piperita L., where menthol was the main component (Pegoraro et al, 2010), regardless of the irradiance level. In contrast, a sharp reduction in phenolic content, particularly of monoterpene hydrocarbons, was observed for thyme cultivated under shade; similarly, the content of thymol, the main essential oil component from plants in full sunlight, was drastically lower forplants in the shade (Letchamo et al, 1994;Letchamo and Gosselin, 1995).…”
Section: Resultsmentioning
confidence: 97%
“…For instance, we found lower content of sabinene, limonene, camphor, isoborneol, (E)-caryophyllene and α-terpineol for plants cultivated under 80% shading, and higher content of α-transbergamotene and cubenol under 50% shading compared to other treatments (Table 2). Likewise, the composition of the essential oil of Hyptis marrubioides varied depending on the radiance level of the environment where plants were grown (Sales et al, 2009). Shading basil plants (Ocimum basilicum L.) did not decrease the oil content but affected the relative composition of volatile compounds (Chang et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…In Aloysia gratissima plants, the essential oil yield in plants grown under full sunlight (0.73 g plant -1 ) and 40% shading (0.88 g plant -1 ) was significantly higher than in those grown at 80% shading (0.26 g plant -1 ) (Pinto et al 2007). In Hyptis marrubioides, the content of essential oil was not influenced by the levels of irradiation (20, 60 and 100% of natural light), but the essential oil yield was higher when plants were grown at the level of 100% irradiation (Sales et al 2009). This result is in agreement with our data, i.e.…”
Section: Short Communicationmentioning
confidence: 92%